Maximum von Mises Stress in the Sliding Contact of Coated Bodies - S. Spinu (Tribology in Industry, 2019)
Competent design decisions for the optimum configuration of a coated contact require the prediction of the stress state developing in the coated body under contact load. Conventional methods of superposition of effects applied in the elasticity of homogenous bodies fail in case of multilayered materials as the response of the latters to point load has only been derived in the frequency domain. A technique for assessment of the elastic response of coated bodies to arbitrary loadings is advanced in this paper, by employing the convolution theorem in the calculation of the stresses and displacements resulting in a sliding contact process. The solution of the elastic frictional contact in full sliding is achieved iteratively, using a state-of-the-art method originally developed for the contact of rough homogenous bodies. Results presented in the literature for the sliding contact of coated bodied are replicated using the newly proposed algorithm. A parametric study is subsequently performed to assess the combined influence of the frictional coefficient, the coating thickness and the elastic modulus mismatch between the coating and the substrate, on the locations and intensity of the maximum von Mises equivalent stress.